PENGARUH PENDAPATAN PERKAPITA DANlTINGKAT PENGANGGURAN TERBUKA TERHADAP KEMISKINANlPROVINSI NUSAlTENGGARAlBARAT - Sanjani, Muhammad Rafi'i (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to determine the effect of Per Capita Income and Open Unemployment on poverty in the province of West Nusa Tenggara. The data used is time series data for the period 2019-2021. This research is associative with the quantitative opinion of the place of implementation in the province of NTB. The data is then analyzed using the Panel data analysis method. The data obtained was then processed using the STATA analysis program version 14. The results showed that partially the Per Capita Income variable (X1) had no significant effect on poverty in the NTB Province, then for the open unemployment variable (X2) it was stated that it had a significant effect on poverty in the NTB Province. Meanwhile, the variable per capita income and open unemployment simultaneously have a significant effect on poverty in the province of NTB.